Adolescent inpatients with anorexia nervosa can roughly predict their own weight trajectories after discharge. Issue 2 (4th March 2022) - Meule, Adrian; Furst Loredo, Artur; Schrambke, Dominic; Schlegl, Sandra; Naab, Silke; Voderholzer, Ulrich
ABSTRACT: Most adolescents with anorexia nervosa (AN) gain a substantial amount of weight during inpatient treatment, but many relapse after discharge. Therefore, there is a need to identify variables that predict weight changes after treatment. The current study tested whether such a variable may be patients' own predictions about their future weight. Data of 120 female adolescent inpatients with AN were available at discharge and one-year follow-up. Patients' own predictions about their future weight trajectories predicted their actual weight change after discharge: those who indicated that they would gain weight, gained weight, those who indicated that they would lose weight, lost weight, and those who indicated to maintain their weight, had no weight change on average. Similarly, expected weight change in kilograms correlated positively with actual weight change after discharge. Thus, patients who expect that they will lose weight again should receive intensified aftercare that fosters motivation to change.